Dynamic Endothelial Stalk Cell–Matrix Interactions Regulate Angiogenic Sprout Diameter - Wang, William Y.; Jarman, Evan H.; Lin, Daphne; Baker, Brendon M. (Frontiers in Bioengineering and Biotechnology, 2021)
Angiogenesis is a complex, multicellular process that involves bidirectional interactions between extracellular matrix (ECM) and collectively invading endothelial cell sprouts that extend the microvasculature during development, wound healing, and disease processes. While many aspects of angiogenesis have been well studied, the relationship between endothelial sprout morphology and subsequent neovessel function remains relatively unknown. Here, we investigated how various soluble and physical matrix cues that regulate endothelial sprouting speed and proliferation correspond to changes in sprout morphology, namely sprout stalk diameter. We found that sprout stalk cells utilize a combination of cytoskeletal forces and proteolysis to physically compact and degrade the surrounding matrix, thus, creating sufficient space in 3D ECM for increasing sprout diameter. As increasing sprout diameter precedes lumenization to generate perfusable neovessels, this work highlights how dynamic endothelial stalk cell-ECM interactions may promote the generation of functional neovessels via sprouting angiogenesis to provide insight into the design of vascularizing implantable biomaterials.